Boron Doped Graphene Quantum Structure and MoS2 Nanohybrid as Anode Materials for Highly Reversible Lithium Storage - Riyanto,; Sahroni, Imam; Bindumadhavan, Kartick; Chang, Pei-Yi; Doong, Ruey-an (Frontiers in Chemistry, 2019)
Herein, the boron-doped graphene quantum structure (BGQS), which contains both the advantages of 0-D graphene quantum dot and 2-D reduced graphene oxide, has been fabricated by top-down hydrothermal method and then mixed with molybdenum sulfide (MoS2) to serve as an active electrode material for the enhanced electrochemical performance of lithium ion battery. Results show that 30 wt% of BGQS/MoS2 nanohybrid delivers the superior electrochemical performance in comparison with other BGQS/MoS2 and bare components. A highly reversible capacity of 3055 mAh g-1 at a current density of 50 mA g-1 is achieved for the initial discharge and a high reversible capacity of 1041 mAh g-1 is obtained at 100 mA g-1 after 50 cycles. The improved electrochemical performance in BGQS/MoS2 nanohybrid is attributed to the well exfoliated MoS2 structures and the presence of BGQS, which can provide the vitally nano-dimensional contact for the enhanced electrochemical performance. Results obtained in this study clearly demonstrate that BGQS/MoS2 is a promising material for lithium ion battery and can open a pathway to fabricate novel 2-D nanosheeted nanocomposites for highly reversible Li storage application.